Optimum Growth and Allocation of Foreign Exchange - Bardhan, Pranab K. (Econometrica, 1971)
[Different policies regarding allocation of foreign exchange to sectors producing grains, tractors, and machine tools give rise to different time profiles of consumption on account of irreversibility of investment. In this paper we try to find the best way this allocation may be done in order to optimize a social objective function over a finite and infinite planning horizon.]